A new species of Raricirrus (Annelida: Cirratuliformia) from deep-water sunken wood off California - Magalhães, Wagner F.; Linse, Katrin; Wiklund, Helena (Zootaxa, 2017)
The genus Raricirrus is characterized by the absence of feeding palps, presence of filamentous branchiae, posterior segments shorter and wider than preceding ones, and by having diverse types of chaetae, including serrate capillaries, long natatory capillaries, falcate and finely pectinate, coarsely serrate chaetae and simple curved spines. A new species of Raricirrus is proposed based on morphological and mitochondrial DNA data. The K2P distance comparison of 16S and COI sequences from Raricirrus specimens collected from sunken wood in the deep-sea (3100 m) off Monterey, California, differed in less than 0.02 in both loci from those of another undescribed Raricirrus species collected at deep-sea hydrothermal vents in the East Scotia Ridge, Southern Ocean, and they are considered conspecific. This species is unique among its congeners by the lack of serrate chaetae, presence of acicular spines and neuropodial capillaries. Raricirrus jennae sp. nov. has only long capillaries on anterior notopodia, straight acicular spines with companion capillaries on posterior notopodia (from chaetigers 15–20), and similar acicular spines and companion capillaries throughout neuropodia. Raricirrus jennae sp. nov. appears to be an opportunistic and widely distributed species. The genus Raricirrus is emended to include the presence of acicular spines and keys to all cirratulid and ctenodrilid genera and Raricirrus species are presented.